Effective Mechanism for Measuring Forces in Tension Member - Filipkowski, Jan; Deska, Krzysztof (Geomatics and Environmental Engineering, 2019)
Tension structures are engineering constructions in which the primary role is played by tension members forming the whole structure or forming its basic elements; e.g., guys. Preserving the right values of the forces in tension members is particularly important for the safe operation of these objects. This paper describes the various direct and indirect methods for determining the forces in the tension members. The basic part of the work is a description of a device that allows us to determine the force of a tension member. The essence of the idea of measuring the force of the tension member using this device is to take over the force of the tension member and then measure it. This device consists among others, of two sets of rope clamps, two annular plates leaning against the clamps, and three steel bars which take over the force of the rope. Changing the length of the rods is recorded using a precision strain meter. In the paper, the realization of the measurement using the device is presented. By measuring the force of a strained tension member using this device, one does not achieve directly the values of the real force but its modified value (which is greater than the real one). The differences between the actual force and the modified one are caused by the length of the mechanism. The constructed device is shown in photographs (Figs. 13 and 14). The measurement of the forces in tension members using this device makes it possible to verify the results of the determination of forces using other methods, for example, using the shape of a tension member which is determined by surveying methods. It is particularly important for the tight, short, nearly vertically disposed guys having relatively large cross-sections.